Efforts to Provide Group Guidance Services to Reduce the Negative Behavior of Puberty Students - Ketaren, Nurdina; Suryani, Ira; Syukri, Makmur (Yana Research, 2023)
Based on the formulation of the research problem, the aims of this study are: (1) To find out the forms of negative puberty behavior of class VII students that occur at SMP Negeri 2 Tanjung Morawa. (2) To find out the efforts made by counseling teachers in providing group guidance services to reduce the negative behavior of puberty students of class VII SMP Negeri 2 Tanjung Morawa. (3) To find out the obstacles in providing group guidance services to reduce the negative behavior of puberty students of class VII SMP Negeri 2 Tanjung Morawa. This research is a type of qualitative research with a descriptive approach. In the process of collecting data, researchers used methods of observation, interviews, and documentation studies. From the results of the study, it can be concluded that the negative forms of puberty behavior of class VII students that have been implemented at Tanjung Morawa 2 Public Middle School are more towards conformity, emotional, boredom, and bullying. The obstacles in implementing group guidance services at SMP Negeri 2 Tanjung Morawa are obstacles in facilities and infrastructure, obstacles in time, obstacles in the stages of implementing group guidance services.